A preliminary factor analytic investigation into the firstorder factor structure of the Fifteen Factor Plus (15FQ+) on a sample of Black South African managers - Seretse Moyo (SA Journal of Industrial Psychology, 2011)
Orientation: The Fifteen Factor Questionnaire Plus (15FQ+) is a prominent personality questionnaire that organisations frequently use in personnel selection in South Africa. Research purpose: The primary objective of this study was to undertake a factor analytic investigation of the first-order factor structure of the 15FQ+.